Crime, Location and the Housing Market - Yves Zenou (The Research Institute of Industrial Economics (IUI), 2005)
We highlight the role of commuting cost, location and housing market in crime decision. By assuming that all crimes are committed in the central business district and that criminals create both positive and negative externalities to each other, we find that high wages or large levels of police resources are a natural way to reduce crime. We also find that bigger cities experience higher levels of crime because of the fiercer competition in the housing market. Finally, we show that reducing commuting costs can also reduce crime because the resulting decrease in housing prices is lower for workers than for criminals.
Keywords: J15; K42; R14; 330; Localized Crime; Housing Market; Commuting Cost; Immobilienmarkt; Pendelverkehr; Kriminalität; Kriminalitätsökonomik